Membangun Keterampilan Adaptasi dan Fokus Belajar di Era Teknologi - Mohamad Azhar Annawa; Wulan Feronika Maharani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The rapid development of technology in recent decades has had a significant impact, on the field of education. The integration of educational technology in today's era emphasizes developing skills such as problem-solving, creativity, collaboration, criticism, and systematic thinking. But with the advancement of technology, it also presents various challenges. The qualitative descriptive method is one of the research methods used to understand a phenomenon in depth by collecting non-numerical data, such as words, images, or documents. This method focuses on describing and interpreting the phenomena being studied, collecting data through observations, interviews, or study of documents. Adapting to digital learning in this technological age where students have to develop independent skills, while teachers play an important role in understanding digital tools and integrating them into the learning process. With the advancement of technology, teachers can also have more varied media choices in learning and can collaborate and develop new skills according to the materials they are taught. It involves the use of techniques such as time blocking to set a specific time for learning, setting up a learning environment that minimizes distractions, using technology wisely, disciplining in using smartphones, and using applications or learning tools that help improve concentration.